2020
DOI: 10.1002/alr.22589
|View full text |Cite
|
Sign up to set email alerts
|

Specific sublingual immunotherapy in children with perennial rhinitis: a systemic review and meta‐analysis

Abstract: Background Allergic rhinitis (AR) is a major public health problem and is increasing worldwide. AR affects children's learning efficiency, sleep quality, and other major aspects of life. Sublingual immunotherapy (SLIT) is effective and safe for children with seasonal AR, but for children with perennial allergic rhinitis (PAR) caused by house dust mites (HDM), its effectiveness and safety is less convincing. Methods Medical literature databases up to 2019 were searched for published and unpublished pieces of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Patient selection seems to be a cornerstone for both the effectiveness and efficiency of SLIT in the long term 2 . However, SLIT has a significantly low risk profile overall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient selection seems to be a cornerstone for both the effectiveness and efficiency of SLIT in the long term 2 . However, SLIT has a significantly low risk profile overall.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory allergies are triggered by allergens that are present in domestic environments (dust, mould) as well as in the external environment (pollen). In this context, specific sublingual immunotherapy (SLIT) provides new and important therapeutic perspectives and represents an approach that is currently available for redirecting the inappropriate immune response in atopic patients 1,2 . SLIT represents an invaluable improvement that can change the clinical history of different types of Immunoglobulin (Ig)E-mediated allergic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2017, numerous SRMAs were identified for SLIT tablets (Table XI.D.6.a.‐1). Eight reported both aqueous and tablet SLIT, 2426,2438,2636,2637,2644,2661–2663 six presented aqueous and tablet SLIT separately, 2438,2550,2638,2639,2664,2665 and nine reported on tablet SLIT alone 1982,1986,1995,2532,2636,2640,2646,2651,2672 . All studies reported outcomes for HDM, grass pollen, and/or ragweed pollen.…”
Section: Managementmentioning
confidence: 99%
“…Studies on SLIT efficacy in children were previously limited by the heterogeneity of trials and the considerable risk of bias 2633 . In addition to the ICAR‐Allergic Rhinitis 2018 evidence demonstrating moderate efficacy for symptom relief in pollen and HDM liquid SLIT 2634 and grass pollen tablet SLIT, 2635 there is additional evidence for a moderate reduction in symptoms and medication scores in pediatric perennial AR 2636,2637 . SLIT efficacy in children is judged to be grade A, with moderate impact.…”
Section: Managementmentioning
confidence: 99%